Biochemical and Fe-resistant characteristics of indigene bacteria from a high iron concentration landfill in Indonesia - Saputri, Purwati; Harahap, Diannita; Lubis , Syafrina S; Ilhami, Syarifa (Narra Sains Indonesia, 2023)
Bacteria isolated from leachate with high heavy metal concentration mostly have potential for bioremediation. The aim of this study was to isolate bacteria from leachate of a landfill containing high concentration of Fe. The leachate sample was collected from Gampong Jawa Landfill, Aceh, Indonesia and used to isolate the bacteria by spread method. The purification of the isolates was carried out through four quadrant plate method. Pure isolates were characterized based on the microscopic or macroscopic appearance and biochemical tests. Fe-resistance was tested by disc diffusion method and constructing the growth curve based on the optical density of broth culture media. A total of 27 pure isolates were obtained and identified, representing eight different genera: Pseudomonas, Bacillus, Neisseria, Micrococcus, Staphylococcus, Proteus, Acinetobacter, and Escherichia. Of eight isolates (each genus was represented by a single isolate), Pseudomonas sp. and Bacillus sp. were considered resistant to Fe exposure (15 ppm) with inhibition zones of 1.00 and 0.81 mm, respectively. At Fe concentration of 20 ppm the inhibition zones exceeded 1 mm, but Bacillus sp. had smaller inhibition zone than that of Pseudomonas sp. (1.15 mm versus 2.86 mm). Growth inhibition of Bacillus sp. was concentration-dependent on Fe exposure but could survive at Fe exposure up to 20 ppm. In conclusion, Bacillus sp. had a resistance against Fe exposure and its bioremediation potential is subjected for future studies.